A Comprehensive Systematic Literature Review on Intrusion Detection Systems - Merve Ozkan-Okay (IEEE, 2021)
Effectively detecting intrusions in the computer networks still remains problematic. This is because cyber attackers are changing packet contents to disguise the intrusion detection system (IDS) recently. Besides, everyday a lot of new devices are added to the computer networks. These new devices are also raising security issues in the computer networks. To effectively manage the computer network flows and provide the security in advance; the components of the IDSs, the approaches and technologies that are used, the nature of the attacks, and the tools that are used needs to be examined deeply. This paper discusses intrusion detection technologies, methodologies, and approaches and also investigates new attack types, protection mechanisms, and recent scientific studies that have been made in this area. In addition, available datasets, well-known IDS tools, and advantages and disadvantages of particular IDSs are explained deeply. We believe that this scientific review study presents a road map for researchers and industry employees who focus on IDSs.